An addendum to “Effects of noise on speech production: Acoustic and perceptual analyses” [J. Acoust. Soc. Am. 84, 917–928 (1988)] - Van Summers, W. (1989)
The authors respond to Fitch’s comments [H. Fitch, J. Acoust. Soc. Am. 86, 2017–2019 (1989) ] on an earlier paper. New analyses are presented to address the question of whether F1 differences observed in the original report are an artifact of linear predictive coding (LPC) analysis techniques. Contrary to Fitch’s claims, the results suggest that the F1 differences originally reported are, in fact, due to changes in vocal tract resonance characteristics. It is concluded that there are important acoustic-phonetic differences in speech when talkers speak in noise. These differences reflect changes in both glottal and supraglottal events that are designed to maintain speech intelligibility under adverse conditions.